Multiple types of hydroxyl-rich cationic derivatives of PGMA for broad-spectrum antibacterial and antifouling coatings. Issue 36 (5th September 2016) - Yuan, Huimin; Yu, Bingran; Fan, Li-Hai; Wang, Meng; Zhu, Yiwen; Ding, Xiaokang; Xu, Fu-Jian
Abstract : A series of hydroxyl-rich quaternized polymers with Ag ions have been proposed for broad-spectrum antibacterial and antifouling coatings. Abstract : The development of new antibacterial materials is a constant demand in the manufacturing of personal hygiene products and medical implements. The inhibition of bacterial adhesion onto surfaces is very challenging, and adhesion may cause secondary infection. In this study, we synthesize multiple types of hydroxyl-rich cationic derivatives via a ring-opening reaction of a star-like poly(glycidyl methacrylate) (s-PGMA) for broad-spectrum antibacterial and antifouling coatings. The derivatives containing tertiary amine groups are subsequently quaternized to produce poly(quaternary ammonium). The quaternary and silver-loaded derivatives exhibit potent and broad-spectrum antibacterial activities towards both Gram-negative and Gram-positive bacteria. Particularly, some of the silver-loaded derivatives show a 64-fold improvement in antibacterial activity toward P. aeruginosa compared to their non-silver counterparts, due to the synergistic actions of quaternary ammonium components and silver ions. Moreover, the antibacterial derivatives can be readily coated on substrates such as glass slides via an adhesive layer of polydopamine. The resultant antibacterial coatings with rich hydroxyl groups also endow antifouling capability against killed bacteria, while the release and diffusion of silver ions from the silver-loaded polymer coatings enable the long-range antibacterial abilities. This study offers a new approach for synthesizing effective antibacterial and antifouling coatings that possess promising applications on biomedical devices.